Bovine tuberculosis diagnosis in the state of Bahia, Brazil, using the multiplex PCR technique - Bruno Ribeiro dos Santos; Bianca Mendes Maciel; Alana Venâncio da Silva; Hllytchaikra Ferraz Fehlberg; Fernando Alzamora Filho (Ciência Animal Brasileira)
The rapid diagnosis of bovine tuberculosis (BT) allows official surveillance institutions to act in areas that could be potential hotspots for the spread of the disease. The study aimed to identify the Mycobacterium bovis agent by multiplex PCR of isolated colonies. Through the official inspection service (Federal/State), samples suggestive of BT were collected during the post-mortem inspection of bovine carcasses in slaughterhouses and sent to the laboratory for complementary diagnostics. The samples were analyzed using bacteriological culture and Ziehl-Neelsen staining. In isolates characterized as Acid-Alcohol Resistant Bacilli (BAAR), the multiplex PCR technique confirmed the agent Mycobacterium bovis. Nine hundred ninety-one thousand three hundred sixteen cattle carcasses were inspected, collecting 32 BT-suggestive samples in from animalsfrom 30 municipalities. Of these, 28.1% (9/32) showed growth on bacteriological culture media with BAAR. The BAAR isolates submitted to multiplex PCR confirmed the presence of M. bovis. The multiplex PCR technique associated with bacteriological examination and applied to post-mortem findings enabled the diagnosis of M. bovis in the municipalities sampled in the Bahia state.